Effect of performance-based pay on employees’ outcomes - Siti Salwa Salim; Azman Ismail (2016)
Based on past research that discussed the system of pay within an organization, participation and performance appraisal are two important elements in a performance-based pay. The ability of managers to implement these two important elements may influence job satisfaction and organizational commitment among employees. Hence, this study was carried out to test the connection between performance-based pay against job satisfaction and organizational commitment. Employees at the Department of Fire and Rescue in Selangor and Putrajaya were chosen as the sample in this study. The outcome of the SmartPLS model analysis demonstrates that participation and performance appraisal play an important role as a determinant of an employee’s job satisfaction and organizational commitment. Discussion, implication, and conclusion have been provided in this study